Features of marketing in tourist branch (Journal of Economic Research & Business Administration, 2015)
Role of marketing is very important in the tourism sector improvement, and in most cases profitable business and action of tourism firms are depend on the right marketing decision. Therefore in the tourism sphere the marketing service has special value. In article the concept and features of marketing in tourist branch is considered. Using of marketing tools in the tourism sphere is shown in the article and given specific proposals.
Keywords: tourism; marketing; guides; industry; firm; market; commodities; consumers